Haemorrhagic colitis associated with enterohaemorrhagic Escherichia coli O165 : H25 infection in a yearling feedlot heifer. Issue 5 (30th October 2015) - Moxley, Rodney A.; Stromberg, Zachary R.; Lewis, Gentry L.; Loy, John D.; Brodersen, Bruce W.; Patel, Isha R.; Gangiredla, Jayanthi
Abstract : Introduction: Enterohaemorrhagic Escherichia coli (EHEC) cause haemorrhagic colitis and haemolytic uraemic syndrome in humans. Although EHEC infection typically results in haemorrhagic colitis in all ages of human patients, in cattle it is usually limited to 1- to 5-week-old nursing calves. Case Presentation: A 1-year-old feedlot beef heifer was moribund with neurological signs and bloody diarrhoea. At necropsy, the colonic mucosa contained multiple grossly visible haemorrhagic erosions, each measuring < 1 mm in diameter. Histologically, foci corresponding to the gross erosions had E. coli O165 antigen-positive bacterial rods adherent to the apical surfaces of degenerate and necrotic colonic mucosal epithelial cells in association with attaching and effacing lesions, and also within cytoplasmic vacuoles in some of these cells. An E. coli O165 : H25 strain was isolated from the colonic mucosal tissue, and by microarray analysis was found to contain virulence genes corresponding to type III secretion system (T3SS) structure and regulation ( cesD, cesT, escD, escF, escN / escV, escR, escT, ler, sepL, sepQ ), T3SS effectors ( espA, espB, espC, espD, espD, espF, espH, espJ, nleB, nleC, nleD, nleH, tir ), serine proteases ( eatA, espC, espP ), Shiga toxin ( stx 2 ), EHEC-haemolysin ( ehxA ), and adhesins [intimin-ϵ ( eae-ϵ ), type 1 fimbria ( fimA, fimB, fimH ), type IV pili ( pilA, pilB, pilC, pilM, pilP, pilQ ) and non-fimbrial adhesin ( efa1 / lifA )]. Conclusion: To the best of our knowledge, this is the first report of disease in cattle associated with EHEC O165 : H25 infection, the oldest bovine EHEC disease case with isolation of the pathogen and the first bovine case to demonstrate grossly evident, haemorrhagic, colonic mucosal erosions associated with EHEC infection.